2012
DOI: 10.3892/etm.2012.527
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of CXCR4 and CD133 proteins is associated with poor prognosis in stage II–III colon cancer patients

Abstract: Although CXCR4 and CD133 have been implicated in the metastatic process of malignant tumors, the clinicopathological significance of their expression in human colon cancer is not fully understood. The present study aimed to examine the expression of the CXCR4 and CD133 proteins in cases of stage II or III colon cancer and the related lymph nodes and to investigate the clinical and prognostic significance of these proteins in colon cancer. Immunohistochemical analysis was performed to examine CXCR4 and CD133 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Hematological malignancy (7 studies, 764 patients) [12-18], breast cancer (18 studies, 4125 patients) [10, 11, 19-34], colorectal cancer (7 studies, 515 patients) [35-41], esophageal cancer (7 studies, 886 patients) [42-48], gastric cancer (5 studies, 755 patients) [49-53], head and neck cancer (7 studies, 577 patients) [54-60], renal cancer (6 studies, 764 patients) [61-66], lung cancer (7 studies, 727 patients) [8, 67-72], melanoma (4 studies, 168 patients) [73-76], gynecologic cancer (8 studies, 826 patients) [9, 77-83], pancreatic cancer (2 studies, 320 patients) [84, 85], prostate cancer (2 studies, 109 patients) [86, 87], liver cancer (2 studies, 256 patients) [88, 89], sarcoma (2 studies, 168 patients) [90, 91] and gallbladder cancer (1 study, 72 patients) [92] were evaluated in current meta-analysis as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematological malignancy (7 studies, 764 patients) [12-18], breast cancer (18 studies, 4125 patients) [10, 11, 19-34], colorectal cancer (7 studies, 515 patients) [35-41], esophageal cancer (7 studies, 886 patients) [42-48], gastric cancer (5 studies, 755 patients) [49-53], head and neck cancer (7 studies, 577 patients) [54-60], renal cancer (6 studies, 764 patients) [61-66], lung cancer (7 studies, 727 patients) [8, 67-72], melanoma (4 studies, 168 patients) [73-76], gynecologic cancer (8 studies, 826 patients) [9, 77-83], pancreatic cancer (2 studies, 320 patients) [84, 85], prostate cancer (2 studies, 109 patients) [86, 87], liver cancer (2 studies, 256 patients) [88, 89], sarcoma (2 studies, 168 patients) [90, 91] and gallbladder cancer (1 study, 72 patients) [92] were evaluated in current meta-analysis as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled model showed a significantly shorter OS with CXCR4 over-expression patients in hematological malignancy (7 studies, 764 patients, HR=1.93, 95% CI, 1.33-2.79, Figure 10) [12-18], breast cancer (18 studies, 4125 patients, HR=1.58, 95% CI, 1.29-1.94, Figure 11) [10, 11, 19-34], colorectal cancer (5 studies, 375 patients, HR=1.83, 95% CI, 1.32-2.53, Figure 12) [36, 37, 39-41], esophageal cancer (7 studies, 886 patients, HR=1.65, 95% CI, 1.24-2.19, Figure 13) [42-48], head and neck cancer (7 studies, 577 patients, HR=2.02, 95% CI, 1.37-2.97, Figure 14) [54-60], renal cancer (5 studies, 594 patients, HR=2.93, 95% CI, 2.06-4.15, Figure 15) [61, 62, 64-66], lung cancer (6 studies, 573 patients, HR=2.51, 95% CI, 1.64-3.83, Figure 16) [8, 67-69, 71, 72], gynecologic cancer (7 studies, 796 patients, HR=2.24, 95% CI, 1.11-4.50, Figure 17) [9, 77-82], liver cancer (2 studies, 256 patients, HR=2.75, 95% CI, 2.02-3.75) [88, 89], prostate cancer (2 studies, 109 patients, HR=2.67, 95% CI, 1.61-4.42) [86, 87] and gallbladder cancer (1 studies, 72 patients, HR=2.30, 95% CI, 1.10-4.80) [92]. Based on the available data, the associations between CXCR4 over-expression and PFS were inconclusive in gastric cancer (5 studies, 755 patients, HR=1.94, 95% CI, 0.86-4.35, Figure 18) [49-53], melanoma (3 studies, 136 patients, HR=1.93, 95% CI, 0.88-4.25, Figure 19) [74-76], pancreatic cancer (2 studies, 320 patients, HR=1.34, 95% CI, 0.63-2.83) [84, 85] and sarcoma (2 studies, 168 patients, HR=5.14, 95% CI, 0.64-41.50) [90, 91].…”
Section: Resultsmentioning
confidence: 99%
“…In Zhang’s study, 125 stage II or III colon cancer specimens without neoadjuvant chemoradiotherapy were obtained after radical resection. 90 patients received postoperative Fu-based adjuvant chemotherapy and 35 stage II patients did not receive adjuvant interventions[48]. Li’s study included 200 colorectal adenocarcinomas and adjuvant chemoradiotherapy was not provided[49].…”
Section: Resultsmentioning
confidence: 99%
“…CXCR4 has been considered as a potential therapeutic target in several studies. A number of in vitro studies have reported that inhibiting the interactions of chemokine CXCR4 using antibodies or small molecules markedly reduces the metastasis of colorectal cancer cells (30,31); this approach could become a promising therapy for colon cancer.…”
Section: Discussionmentioning
confidence: 99%